2022
DOI: 10.1007/s10518-022-01489-7
|View full text |Cite
|
Sign up to set email alerts
|

Loss of support assessment for precast portal frames with friction connections and masonry infills

Abstract: The loss of support of beam elements in Italian precast buildings is one of the main vulnerabilities recorded in past earthquakes. The reason for beam falling is due to the absence of adequate structural details in the beam-column joints, which were typically relying on friction for buildings located in regions previously classified as non-seismic prone. To guarantee the structural safety of the whole existing building stock, this collapse mechanism must be further investigated; in this regard, it could be int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The seismic risk associated with one-storey existing precast buildings has been studied in various works [18,19,20,21,15]. The results obtained confirm the need to implement retrofit interventions to protect working activities and human lives.…”
Section: Introductionmentioning
confidence: 74%
“…The seismic risk associated with one-storey existing precast buildings has been studied in various works [18,19,20,21,15]. The results obtained confirm the need to implement retrofit interventions to protect working activities and human lives.…”
Section: Introductionmentioning
confidence: 74%
“…Finally, it is worth noting that the modelling strategies proposed may also be adopted in future research for the assessment of the structural behaviour of reference buildings in case of aftershocks (Poiani et al 2020). An aftershock may lead to an increase in the damage pattern especially in the case of the loss of the support of the structural elements such as in the presence of friction connections (Labò et al 2022).…”
Section: Loss Assessmentmentioning
confidence: 99%
“…The main beams are generally prestressed and supported to the columns through either dowel connections (Clementi at al., 2016;Zoubek et al, 2015;Kremmyda et al, 2014) or simple bearing (Casotto et al, 2015;Demartino et al, 2018;Ercolino et al, 2016;Bosio et al al., 2020;Labò et al, 2022); the latter is found for old buildings not designed for seismic actions, where friction was considered sufficient for the horizontal load transfer. The roof elements are generally made of long span precast double-tee or winged beams simply supported on the main girders and connected through mechanical systems or simple friction, for new or old buildings, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…20 A ductile behavior can be achieved by subdividing the infill wall into subpanels with sliding joints constructed by sliding materials 21,22 or dampers. 23,24 These methods indeed improve the deformation and bearing capacities of the infill walls 25 ; however, the intervention of door openings into these infill walls might interrupt their intended functionality. [26][27][28] To address these challenges in the field, three primary approaches have emerged: strength improvement of the infill and/or the door openings, uncoupling the infill from the surrounding frames, and construction of a sliding mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Separating the infill wall from the boundary frame could mitigate the adverse interaction, 19 while this method may compromise the out‐of‐plane capacity of the infill wall 20 . A ductile behavior can be achieved by subdividing the infill wall into subpanels with sliding joints constructed by sliding materials 21,22 or dampers 23,24 . These methods indeed improve the deformation and bearing capacities of the infill walls 25 ; however, the intervention of door openings into these infill walls might interrupt their intended functionality 26–28 …”
Section: Introductionmentioning
confidence: 99%